Answer:
x = 7
Step-by-step explanation:
given equation is :
14x-49 = x²
adding -x² to both sides of equation,we get
-x²+14x-49 = -x²+x²
-x²+14x+49 = 0
take -1 as common
-1(x²-14x-49) = 0
now multiplying above equation to -1, we get
x²-14x-49 = 0
now, above equation is in general equation.
split the middle term of above equation so that the product of two terms should be 49 and sum be -14.
x²-7x-7x-49 = 0
make two groups
x(x-7)-7(x-7) = 0
take (x-7) as common
(x-7)(x-7) = 0
now applying zero-product property to above equation,we get
x-7 = 0 or x-7 = 0
as both are same ,hence
x-7 = 0
adding 7 to both sides of above equation,we get
x-7+7 = 0+7
x+0 = 7
x = 7 which is the answer.
Plz mark me brainliest!!!